Antinflammatory Effects of Allergen Immunotherapy - Incorvaia, Cristoforo; Mauro, Marina; Rapetti, Andrea; Frati, Franco (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2008)
The most common allergic diseases, such as rhinitis, asthma, and atopic dermatitis, are caused by inflammation induced by an immune response to environmental allergens, driven by regulatory cells such as antigen presenting cells and T lymphocytes with their secreted products of multiple activities - cytokines and chemokines - and sustained by effector cells such as mast cells, basophils, and eosinophils. Allergen immunotherapy (AIT) is the only treatment able to modify the natural history of allergy, and a bulk of evidence is available on its effects on allergic inflammation. The antinflammatory effects of AIT rely upon the ability to modify the phenotype of T cells, which recognize in allergic subjects a prevalence of the Th2 type and its cytokine pattern, characterized by production of IL-4, IL-5, IL-13, IL-17, and IL-32. The immunotherapy-induced changes result in a Th1-type response (immune deviation) related to an increased IFN-gamma and IL-2 production or by a Th2 reduced activity, through a mechanism of anergy or tolerance. A number of studies showed that T cell tolerance is characterized by the generation of allergen-specific T regulatory (Treg) cells, which produce cytokines such IL-10 and TGF-beta with immunosuppressant and/or immunoregulatory activity. Recent studies suggest that the antinflammatory mechanism is similar in the two forms of subcutaneous and sublingual immunotherapy, with a particular role in the latter for mucosal dendritic cells. The tolerance pattern induced by Treg accounts for the suppressed or reduced activity of inflammatory cells such as mast cells, basophils and eosinophils and for the isotypic switch of antibody synthesis from IgE to IgG, and especially IgG4, which were early thought to be the major effects of AIT but now must be view in the frame of a general model.
Keywords: T cells